Effect of human and technology interaction: computer vision syndrome among administrative staff in a public university - Zainuddin, Huda; Muhammad Isa, Muhammad (Centre for Promoting Ideas, 2014)
Introduction: Computer vision syndrome is a complex of eye and vision problems related to near work experienced during computer use. A cross-sectional study was done to determine the prevalence of computer vision syndrome, knowledge and attitude on visual ergonomics among administrative staff in Universiti Putra Malaysia (UPM). Material and Methods: Apre-tested, self-administered questionnaire was distributed to 216 administrative staffs in 10 randomly selected faculties in UPM. Results: Of 146 respondents, a total of 92 (63%) respondents had computer vision syndrome. A proportion of the respondents (35.6%) had poor level of knowledge, while 50% had poor attitude on visual ergonomics. There was significant association between gender and level of knowledge on visual ergonomics (p=0.003). Conclusion: Computer vision syndrome is prevalent among the administrative staff. Preventive strategy such as trainings on visual ergonomics should be organized by the management.